A diversification case of heptapterine catfishes (Siluriformes, Heptapteridae) in the Magdalena basin, Colombia (2022)
ABSTRACT: The Magdalena River forms one of the most extensive basins in northwestern South America. In spite of having a relatively low taxonomic richness of fishes (236 species) compared with similar-sized basins in the continent, holds one of the highest level of endemicity for any Neotropical basin (65%). Most of the main fish lineages distributed in this basin represents either relicts of widespread groups that are currently more diversified in cis-Andean basins or more restricted taxa exclusively distributed in trans-Andean basins. Here we present a remarkable example of this last case, represented by a lineage of small heptapterine catfishes exclusively distributed in the Magdalena basin. DNA barcode delimitation analyses revealed five undescribed species that were traditionally believed to represent a single species for the entire basin. These five species were found to form a well-supported monophyletic group in a phylogenetic analysis of 1069 ultraconserved elements loci . The Magdalena lineage is placed sister to Phenacorhamdia, en exclusive cis-Andean genus. The monophyly of the Magdalena lineage is supported by exclusive synapomorphies and some characters previously believed to be synapomorphies of Phenacorhamdia were found to support its sister relationship to the Magdalena lineage. This sister pair was found to form a clade with Pariolius (another cis-Andean genus), which together are sister to Cetopsorhamdia, a genus with a wide geographic distribution in the continent and that includes some species from the Magdalena basin. Thus, this phylogenetic arrangement suggests a complex biogeographic scenario in the evolutionary history of heptapterine catfishes.